2018
DOI: 10.1590/s1984-29612018001
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninum in properties in the west region of Paraná, Brazil: prevalence and risk factors

Abstract: Neospora caninum is a heteroxenous protozoa, whose definitive hosts are canids and intermediate hosts are herbivores, and is of great importance in cattle. The objectives of this study were to determine the prevalence of N. caninum in dairy cattle and dogs, to detect the presence of the protozoa at the molecular level in aborted fetuses, and to identify the risk factors associated with infection in properties in the western region of the state of Paraná. For this study, 600 bovine serum samples from 60 propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
4
7
0
2
Order By: Relevance
“…Our work further reinforces the relationship between abortion and N. caninum seropositivity, but we must not forget that T. gondii was also identified as a risk factor associated with abortion, so this etiological agent should also be included as a differential in reproductive cases of this species. Snak et al (2018), studying dairy properties in Western Paraná, found as a risk association with N. caninum low milk production, which corroborates with our study, as we detected properties with more than 10 animals acting as a protective association with T. gondii. We can consider that these farms with more than 10 lactating animals use or seek technologies to increase livestock production, resulting in better herd health, a fact that may explain the protection factor found.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our work further reinforces the relationship between abortion and N. caninum seropositivity, but we must not forget that T. gondii was also identified as a risk factor associated with abortion, so this etiological agent should also be included as a differential in reproductive cases of this species. Snak et al (2018), studying dairy properties in Western Paraná, found as a risk association with N. caninum low milk production, which corroborates with our study, as we detected properties with more than 10 animals acting as a protective association with T. gondii. We can consider that these farms with more than 10 lactating animals use or seek technologies to increase livestock production, resulting in better herd health, a fact that may explain the protection factor found.…”
Section: Resultssupporting
confidence: 92%
“…Snak, Garcia, Lara, Pena and Osaki (2018) studying the agent detected a prevalence of IgG immunoglobulin of 23.7% in dairy cattle in the western region of the state. When analyzing occurrence by property, Locatelli-Dittrich et al (2008) found 77% positivity and Snak et al (2018) reported 80% of farms with at least one positive animal. The authors mentioned above showed high rates when compared with the present study in both animals and properties; this reveals the diversity of the level of protozoan infection in our state.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of anti-NC antibodies detected in the present study when the total serum samples were analyzed (22.75%) is in accordance with serological studies realized in some Brazilian regions/states, as Goiás (27%) (SANTIN et al, 2017) and Paraná (13.2%) (Snak et al 2018). There was not statistical difference in the frequency detection of antibody anti-NC in animals naturally infected with BVDV (23.27%) and not infected (21.18%), suggesting that in the bovines tested, the frequency of animals persistently infected with N. caninum should not be influenced by previously BVDV infection.…”
Section: Resultssupporting
confidence: 91%
“…The differences on seroprevalence in each part of the country may be as a result of various factors like sampling and investigation methods, farms management, food storage, contact with carnivores, geographic conditions, and temperature effect on viability and sporulation of N. caninum oocysts. This finding was also similar to the reports in Kenya, Brazil and Slovakia ( Dubey et al., 2007 , Okumu et al., 2019 , Snak et al., 2018 ).…”
Section: Discussionsupporting
confidence: 92%